2004
DOI: 10.4049/jimmunol.173.3.2099
|View full text |Cite
|
Sign up to set email alerts
|

Smad3 Null Mice Develop Airspace Enlargement and Are Resistant to TGF-β-Mediated Pulmonary Fibrosis

Abstract: Transforming growth factor-β1 plays a key role in the pathogenesis of pulmonary fibrosis, mediating extracellular matrix (ECM) gene expression through a series of intracellular signaling molecules, including Smad2 and Smad3. We show that Smad3 null mice (knockout (KO)) develop progressive age-related increases in the size of alveolar spaces, associated with high spontaneous presence of matrix metalloproteinases (MMP-9 and MMP-12) in the lung. Moreover, transient overexpression of active TGF-β1 in lungs, using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

25
267
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 354 publications
(293 citation statements)
references
References 64 publications
25
267
0
1
Order By: Relevance
“…At the level of gene expression, we noticed that the duration of TIMP-1 upregulation following AdTGF-β3 was transient and returned to baseline by day 14, while this gene was persistently induced in AdTGF-β1 treated rats. These findings strongly support previous reports showing that transient fibrosis in the lungs following CTGF overexpression or using bleomycin or AdTGF-β1 in fibrosis resistant mice were accompanied by low levels of TIMP-1 gene induction (Bonniaud et al, 2004;Kolb et al, 2002).…”
Section: Discussionsupporting
confidence: 92%
“…At the level of gene expression, we noticed that the duration of TIMP-1 upregulation following AdTGF-β3 was transient and returned to baseline by day 14, while this gene was persistently induced in AdTGF-β1 treated rats. These findings strongly support previous reports showing that transient fibrosis in the lungs following CTGF overexpression or using bleomycin or AdTGF-β1 in fibrosis resistant mice were accompanied by low levels of TIMP-1 gene induction (Bonniaud et al, 2004;Kolb et al, 2002).…”
Section: Discussionsupporting
confidence: 92%
“…Although studies by our group [12] and others [36] have shown the capacity of TGF-β1 to activate FAK in certain cell types, a role for SMAD3 in mediating this effect has not been previously demonstrated. The requirement for SMAD3 in FAK activation is consistent with a role for SMAD3 in myofibroblast differentiation both in-vitro [37,38] and in-vivo [39][40][41].…”
Section: Discussionsupporting
confidence: 73%
“…Data TGF-b signaling in prostate cancer reactive stroma F Yang et al presented here are consistent with the implication of Smad3 in mediating wound healing and fibrosis. As might be predicted, Smad3 null mice were refractory to TGF-b1-induced pulmonary fibrosis (Bonniaud et al, 2004). However, the function of Smad3 in mediating TGF-b-induced responses in cancer-associated reactive stroma biology is poorly understood.…”
Section: Discussionmentioning
confidence: 95%